The Mediating Effects of Self-Concept in the Relationship of Brand Image and Purchasing Buying Behavior - Eric S Parilla; Marc Edward Abadilla (Research Synergy Foundation, 2023)
This study aims to determine the effect of brand image on purchasing buying behavior. It proposes self-concept as a mediating variable and answers how brand image affects purchasing behavior. The study has implications for marketing management, such as for advertisers who intend to measure how to promote skincare products for men. The original contribution of this study lies within its questionnaire that has been attuned to the effects of brand image on purchasing behavior. To answer the research questions, this study used structural equation modeling. The output revealed a mediating effect of self-concept in the association between brand image and purchasing behavior.